The geoeconomic regions of the Cerrado (Brazilian Savanna): The geoeconomic regions of the Cerrado (Brazilian Savanna) (Élisée - Revista de Geografia da UEG, 2023)
The Cerrado (Brazilian Savanna) is a mosaic of ecological environments whose territorial appropriation also took place in a fragmented way. In order to delimit these socio-spatial differences and inequalities, we propose a division of the Cerrado into 11 regions, based on environmental, economic and historical aspects, in particular the territorialization of agricultural production of commodities. Each region was described according to the determinations of its place in the territorial division of labor.
Keywords: Cerrado. Brazilian Savanna. Regionalization. Territorial division of labor.